Adaptive Web Based Application Development (International Journal of Engineering and Computer Science, 2017)
The World Wide Web has had an extremely significant impact on access to information and information services. Web-based applications are influencing many domains such as business, commerce, banking and learning. The Web has simplified access to information and information services, enabling a variety of users with different backgrounds, social situations, and so on to participate. The increasing complexity of such applications calls for engineering methods for developing efficient high quality software applications with all the appropriate performance, features and services which are required. Applications and information which are provided on the Web according to the ‘one size fits all’ approach are not appropriate to such a heterogeneous environment. Adaptive Web-based applications are an alternative to the traditional “one-size fits-all” static approach in the development of applications. Thus a distinctive feature of such an adaptive application is its ability to adapt itself to certain conditions.